Enhancing Creativity and Numeracy in Primary Science Learning: A STEAM-Based IPAS Approach for Fifth-Grade Students at SD Negeri Mijen 2 - Aulia Zulfa (CV. Ulil Albab Corp, 2026)
This study aims to examine the effectiveness of STEAM-based IPAS instruction in improving students’ creativity and numeracy skills in primary science learning. The research employed a pre-experimental one-group pretest–posttest design involving 19 fifth-grade students of SD Negeri Mijen 2. Numeracy skills were measured using a validated numeracy test aligned with AKM indicators, while creativity was observed through structured performance rubrics. Data were analyzed using descriptive statistics, normality testing, and paired-sample t-tests. The results indicate a significant improvement in students’ numeracy achievement, with the mean pretest score of 61.47 increasing to 78.95 in the posttest, representing a gain of 17.48 points or 28.4%. Statistical analysis revealed a significant difference between pretest and posttest scores (t(18) = 9.27, p < 0.001). These findings demonstrate that STEAM-based IPAS instruction effectively enhances numeracy skills and supports creative learning processes in primary science education.